Kepemimpinan Transformasional dan Organizational Citizenship Behavior (OCB) Dampaknya Pada Kinerja Organisasi - Dirga Lestari (Akutansi Bisnis & Manajemen ( ABM ), 2014)
One of important contributor to make the performance?s organization is leadership behavior. There are many ways to influence followers transformational leadhership by putting the power charismatic, inspirational motivation and personal approach in achieving superior employee performance employee. Transformational effective leadhership emphasize a sense of voluntary and willingness to work even beyond its responsibility of organizational citizenship behavior (OCB). The purposive of this research is to examine transformational leadhersip style which can affect Organizational Citizenship Behavior and organizational performance. Data collect from a unit at the office kabupaten X which consists of 12 units of work with a sampel of 161 respondents. The result showed that the leadhersip behavior transformational have significant Organizational Citizenship Behaviorand and indirectly have an influence in in the organizational performance. Whereas Organizational Citizenship Behaviordirecly influence significant organizational performance. This finding confirms that OCB is intervening variables that relations between the leadhership of the performance of organizational.